Coexistence of epilepsy and poliomyelitis: assessment of the clinical and pathophysiological relationship - Demir, C.; Berilgen, M. S.; Mungen, B.; Bulut, S. (Springer Heidelberg, 2010)
[Abstract Not Available]
20th Meeting of the European-Neurological-Society -- JUN 19-23, 2010 -- Berlin, GERMANY